2012
DOI: 10.1095/biolreprod.112.102905
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative Effect of Histamine on MA-10 Leydig Tumor Cells Mediated Through HRH2 Activation, Transient Elevation in cAMP Production, and Increased Extracellular Signal-Regulated Kinase Phosphorylation Levels1

Abstract: Mast cells (MC) occur normally in the testis with a species-specific distribution, yet their precise role remains unclear. Testicular MC express histidine decarboxylase (HDC), the unique enzyme responsible for histamine (HA) generation. Evidence to date supports a role for HA as a local regulator of steroidogenesis via functional H₁ and H₂ receptor subtypes (HRH1 and HRH2, respectively) present in Leydig cells. Given that HA is a well-known modulator of physiological and pathological proliferation in many diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 50 publications
3
23
2
Order By: Relevance
“…The existence of a functional histaminergic system in the testis of different species has been demonstrated previously by us (Mondillo et al 2005, Pagotto et al 2012 and others (Mayerhofer et al 1989, Pap et al 2002, Albrecht et al 2005, Khan & Rai 2007. Particularly, we have reported that low concentrations of HA (10 K9 M) stimulate LC steroidogenesis and higher concentrations (10 K5 M) inhibit it (Mondillo et al 2005).…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…The existence of a functional histaminergic system in the testis of different species has been demonstrated previously by us (Mondillo et al 2005, Pagotto et al 2012 and others (Mayerhofer et al 1989, Pap et al 2002, Albrecht et al 2005, Khan & Rai 2007. Particularly, we have reported that low concentrations of HA (10 K9 M) stimulate LC steroidogenesis and higher concentrations (10 K5 M) inhibit it (Mondillo et al 2005).…”
Section: Discussionsupporting
confidence: 63%
“…In this respect, it has been shown that HA can act as both an anti-mitogenic (Cricco et al 2006, Petit-Bertron et al 2009, Meng et al 2011) and a mitogenic (Molina-Hernandez & Velasco 2008, Francis et al 2009, Medina et al 2011, Stoyanov et al 2012 agent, depending on the cell type and the HA receptor pattern expressed. In particular our recent studies have shown, for the first time to our knowledge, the proliferative effect of HA in MA-10 LCs, mediated via HRH2 activation and increased cAMP production and ERK phosphorylation (Pagotto et al 2012).…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Accordingly, numerous studies from our group and others over the past few years have documented the ability of HA to modulate Leydig cell steroidogenesis through HRH1 and HRH2 (Mayerhofer et al 1989, Mondillo et al 2005, 2007, Khan & Rai 2007, and a very recent publication from our group has suggested a role for HA as an autocrine-paracrine regulator of Leydig cell proliferation under testicular pathological conditions (Pagotto et al 2012). Considering that germ cells express HDC (Safina et al 2002), and that HA has been implicated in spermatogenesis, penile erection and sexual behavior as well as steroidogenesis (Cara et al 1995, Par et al 2003, Sinha et al 2006), it appears that the amine plays an integral role in the regulation of male reproductive function, which certainly deserves further investigation.…”
Section: Introductionmentioning
confidence: 89%